The Influence of Digital Marketing on Consumer Purchase Decisions of Shopee Application Users - Rettobjaan, Vitalia Fina Carla; Aristayudha, AA Ngurah Bagus; Astitiani, Ni Luh Putu Surya; Widnyani, Ni Made (Journal of Economics and Public Health, 2024)
The development of e-commerce in Indonesia is increasing, slowly people are starting to abandon conventional shopping habits and switch to online shopping. E-commerce is used as a solution as a buying and selling medium that can save time and costs. Shopee is an e-commerce company that already has a name and is one of the big players in the business world. Purpose: The purpose of this research is to determine the influence of digital marketing on Shopee application users on purchasing decisions. This research is an analytical observational study with a cross sectional approach. The sample used in this research was 100 Bali International University students who were calculated using the Slovin formula. The sampling technique uses Consecutive Sampling. The data collection tool uses a questionnaire and the results are then analyzed using Path Analysis. Validity and reliability tests were carried out to ensure that the instruments used in this research had a high level of accuracy and consistency. Website, search engine marketing, web banner, social network and affiliate marketing variables have a significant influence on consumer purchasing decisions using the Shopee case study application at Bali International University with a total determination value of 0.761. Digital marketing is reaching as many consumers as possible in an efficient manner through various web-based media such as blogs, websites, emails, AdWords or social networks.